Development of a methodology for selecting criteria and indicators of sustainable forest management: a case study on participatory assessment - Mendoza, G.A.; Prabhu, Ravi (2000)
This paper describes an application of multiple criteria analysis (MCA) in assessing criteria and indicators adapted for a particular forest management unit. The methods include: ranking, rating, and pairwise comparisons. These methods were used in a participatory decision-making environment where a team representing various stakeholders and professionals used their expert opinions and judgements in assessing different criteria and indicators (C&I), and how suitable and applicable they are to a forest management unit. A forest concession located in Kalimantan, Indonesia, was used as the site for the case study. Results from the study show that the multi-criteria methods are effective tools that can be used as structured decision aids to evaluate, prioritise, and select sets of C&I for a particular forest management unit. Ranking and rating approaches can be used as a screening tool to develop an initial list of C&I. Pairwise comparison, on the other hand, can be used as a finer filter to further reduce the list. In addition to using these three MCA methods, the study also examines two commonly used group decision-making techniques; the Delphi method and the nominal group technique. Feedback received from the participants indicates that the methods are transparent, easy to implement, and provide a convenient environment for participatory decision-making.